Effect of sintering temperature on the structure and mean crystallite size of Zn1-xCoxO (x = 0.01 – 0.05) samples (Superficies y Vacío, 2014)
In this work, powders were prepared Zn1-xCoxO (0.00 ? x ? 0.05) at temperatures of calcination of 773, 823, and 873 K by sol gel methods (citrate route). In the XRD patterns, all the observed diffraction peaks could be indexed to ZnO wurtzite structure, and no other impurity phase was found, leading to the conclusion that the Co ions in fact entered into ZnO crystal. Rietveld analysis shows that all samples have a hexagonal wurtzite structure with mean lattice constants a = 3.2507 A? and c = 5.2073 A?, and that no important changes of the lattice parameters were observed as a consequence of Co doping or temperature of calcination. The average crystallite size was measured using Scherrer’s method, and the results show that when Co concentration increased from 0 to 5%, crystallite size varied depending on the sample calcination temperature (Tc). In general, the lower the Tc, the higher the crystallite size, and at a particular Tc, the higher the Co concentration, the higher the crystallite size. The last one suggests the promotion of crystal growth as a result of Co doping in ZnO at least for the synthesis method used here. Raman spectroscopy results showed an increase of the defect concentration as a consequence of an increase in Co contents.